The importance of cultural leadership during post-acquisition integration - Mcconnon, Tom (2013)
Mergers and acquisitions (M&A) are not only financial decisions but can also be understood as social processes. Due to the myriad of changes generated by an acquisition, the integration period is characterised by multiple adjustment difficulties. A substantive body of research blames post-acquisition ‘cultural clash’ caused by cultural differences between the two merging organisations as a major cause of disappointing integration outcomes. Yet research into the process of cultural leadership during the integration phase of an acquisition has only been sporadically studied. In fact no study to date has tackled the question of cultural leadership post-acquisition from the perspective of M&A advisory firms. Through the analysis of four interviews with M&A advisory consultants, this novel study examines the concept of cultural leadership post-acquisition. The results explore the key mechanisms through which Trice and Beyer’s (1993) two variants of cultural leadership – leadership that changes and integrates cultures – are exercised to bring about the successful integration of the acquired organisation. Our findings have significant implications for future organisations that wish to pursue acquisitions. It is hoped organisations will be better able to anticipate cultural clash and in doing so, tailor leadership programs to address there underlying roots, ultimately augmenting integration success.